2002
DOI: 10.1677/joe.0.175r001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ghrelin concentrations in elderly subjects: comparison with anorexic and obese patients

Abstract: Ghrelin, a novel endogenous ligand for the GH secretagogue receptor, has been reported to stimulate GH secretion and food intake in both humans and other animals. Interestingly, recent data indicate that ghrelin is up-and down-regulated in anorexia nervosa (AN) and obesity, which are also known to be accompanied by increased and reduced GH levels respectively. Ageing is associated with a gradual but progressive reduction in GH secretion, and by alterations in appetite and food intake. The role of ghrelin in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
137
5
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(155 citation statements)
references
References 37 publications
12
137
5
1
Order By: Relevance
“…Since the activity of nitric oxide synthase is diminished in aging (although human data are not conclusive), it may explain lower activity of ghrelin in older people. Another finding is that older persons have lower levels of acylated (orexigenic) ghrelin compared to desacylated (anorexigenic, although this is controversial) ghrelin (Rigamonti et al 2002). Sturm et al found that plasma ghrelin concentrations were much higher in the undernourished older women than in well-nourished older women and wellnourished young women, and ghrelin concentrations decreased more after food ingestion in the older compared with the young subjects (Sturm et al 2003).…”
Section: Gastrointestinal Hormonesmentioning
confidence: 99%
“…Since the activity of nitric oxide synthase is diminished in aging (although human data are not conclusive), it may explain lower activity of ghrelin in older people. Another finding is that older persons have lower levels of acylated (orexigenic) ghrelin compared to desacylated (anorexigenic, although this is controversial) ghrelin (Rigamonti et al 2002). Sturm et al found that plasma ghrelin concentrations were much higher in the undernourished older women than in well-nourished older women and wellnourished young women, and ghrelin concentrations decreased more after food ingestion in the older compared with the young subjects (Sturm et al 2003).…”
Section: Gastrointestinal Hormonesmentioning
confidence: 99%
“…[4][5][6] Reduced levels have been reported in obese subjects, 7,8 whereas increased concentrations have been found in patients with anorexia nervosa. 8,9 A preprandial rise 10 and a postprandial fall 11 in ghrelin levels indicate a physiological role of food on ghrelin secretion in humans. However, in obese subjects, food fails to suppress ghrelin levels, 12,13 or has an impaired suppressive effect compared with normal weight controls.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a decline in plasma ghrelin with age has also been reported (Serra-Prat et al 2007), and several groups, including ours, have investigated the role of ghrelin in the elderly in relation to metabolic syndrome (MS), hunger and satiety (Rigamonti et al 2002;Serra-Prat et al 2009a, b). Ghrelin circulating concentrations decline in old people may contribute to the phenomenon called 'anorexia of ageing' and influence nutritional impairment development.…”
mentioning
confidence: 74%